2021
DOI: 10.1021/acspolymersau.1c00036
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Electron Transfer and Changes in Surface Free Energy in Polythiophene-Polyviologen Bilayered Thin Films

Abstract: Bipyridiniums, also known as viologens, are well-documented electron acceptors that are generally easy to synthesize on a large scale and reversibly cycle between three oxidation states (V2+, V•+, and V0). Accordingly, they have been explored in a number of applications that capitalize on their dynamic redox chemistry, such as redox-flow batteries and electrochromic devices. Viologens are also particularly useful in photoinduced electron transfer (PET) processes and therefore are of interest in photovoltaic ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Understanding PET in the active materials for organic electronics, mainly for photovoltaic applications, is crucial for better device efficiency. For solar cells, electron transfer followed by exciton splitting is desired to collect the charge carriers at the respective electrodes. Donor–acceptor systems having suitable redox potentials have shown photoinduced intramolecular or intermolecular electron transfer. From these studies it has been found that PET is affected by several factors such as (i) the electronic structures of the donor and acceptor, (ii) the distance between them, and (iii) environmental effects such as the solvent in solution and the morphology in the solid state. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding PET in the active materials for organic electronics, mainly for photovoltaic applications, is crucial for better device efficiency. For solar cells, electron transfer followed by exciton splitting is desired to collect the charge carriers at the respective electrodes. Donor–acceptor systems having suitable redox potentials have shown photoinduced intramolecular or intermolecular electron transfer. From these studies it has been found that PET is affected by several factors such as (i) the electronic structures of the donor and acceptor, (ii) the distance between them, and (iii) environmental effects such as the solvent in solution and the morphology in the solid state. …”
Section: Introductionmentioning
confidence: 99%
“…Photoexcited electron transfer in organic dyes and transition metal complexes has been studied by several research groups because of their photophysical properties. In these systems, electron transfer either from the organic dye or from the metal center in both directions has been studied. Different families of organic dyes, including perylene diimides (PDIs), have been studied to explore PET. PDIs offer a high absorption coefficient, photostability, and ease of synthetic manipulation, making them suitable for various applications involving electron transfer. PDI derivatives attached to a heteroleptic iridium complex were used to show single-electron oxidation of a catalyst precursor for water oxidation, and a D–A system involving PDI was demonstrated to show excellent power conversion efficiency in organic solar cells .…”
Section: Introductionmentioning
confidence: 99%
“…25,26 Since a volume change in the gel occurred during the reduction process, the actuator could work only under anaerobic conditions inside a N 2 -filled glovebox. 25,27,28 This is a serious drawback for practical application. Based on this perspective, we aim to develop the foldamerbased gel actuators that also function under aerobic conditions (under oxidative conditions in air).…”
Section: Introductionmentioning
confidence: 99%
“… Barnes et al reported on the redox-responsive actuation of the hydrogel consisting of linearly connected viologen polymers . When the viologen unit was reduced to the radical cation state, the conformation of the viologen polymer was found to alter from the extended state to the folded state due to the radical-based self-assembly of the viologen units. , Since a volume change in the gel occurred during the reduction process, the actuator could work only under anaerobic conditions inside a N 2 -filled glovebox. ,, This is a serious drawback for practical application.…”
Section: Introductionmentioning
confidence: 99%